Disruption of the VAPB-PTPIP51 ER-mitochondria tethering proteins in post-mortem human amyotrophic lateral sclerosis - Hartopp, Naomi; Lau, Dawn H W.; Martin-Guerrero, Sandra M.; Markovinovic, Andrea; Mórotz, Gábor M.; Greig, Jenny; Glennon, Elizabeth B.; Troakes, Claire; Gomez-Suaga, Patricia; Noble, Wendy; Miller, Christopher C.J. (Frontiers in Cell and Developmental Biology, 2022)
Signaling between the endoplasmic reticulum (ER) and mitochondria regulates many neuronal functions that are perturbed in amyotrophic lateral sclerosis (ALS) and perturbation to ER-mitochondria signaling is seen in cell and transgenic models of ALS. However, there is currently little evidence that ER-mitochondria signaling is altered in human ALS. ER-mitochondria signaling is mediated by interactions between the integral ER protein VAPB and the outer mitochondrial membrane protein PTPIP51 which act to recruit and “tether” regions of ER to the mitochondrial surface. The VAPB-PTPI51 tethers are now known to regulate a number of ER-mitochondria signaling functions. These include delivery of Ca2+ from ER stores to mitochondria, mitochondrial ATP production, autophagy and synaptic activity. Here we investigate the VAPB-PTPIP51 tethers in post-mortem control and ALS spinal cords. We show that VAPB protein levels are reduced in ALS. Proximity ligation assays were then used to quantify the VAPB-PTPIP51 interaction in spinal cord motor neurons in control and ALS cases. These studies revealed that the VAPB-PTPIP51 tethers are disrupted in ALS. Thus, we identify a new pathogenic event in post-mortem ALS.